Developing systems thinking of Thai grade 11 students through model-based learning with concept mapping - Kongped, Tanakon; Cojorn, Kanyarat (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This action research aimed to develop systems thinking skills of Thai grade 11 students through model-based learning with concept mapping. The research was designed using an action research approach, focusing on students who faced challenges with the subject matter. Participants included 32 grade 11 students from a public high school in northeastern Thailand. The study utilized a learning management plan that incorporated nine sub-lessons, structured into three learning cycles. The instruments included the model-based learning with concept map learning management plan, a systems thinking assessment, a systems thinking rubric, and a classroom behavior observation form. Results indicated a continuous improvement in students’ systems thinking skills from learning cycle 1 to 3, with an increasing number of students meeting the performance threshold. When examining each aspect, it was found that in cycles 1 and 3, the highest average scores were in root cause analysis, while the lowest were in the feedback. In cycle 2, the highest average scores were also in root cause analysis, while the lowest were in causal loop. The model-based approach provided students with a mechanism to develop a better understanding, while the concept maps helped them connect the content and reinforce what they had learned. This study contributes to the field of science education by providing evidence that supports the use of model-based learning and concept mapping to enhance systems thinking among high school students.